THE EFFECT OF AERATION ON THE DISTRIBUTION OF MICROALGAE CONCENTRATE - Ludi Parwadani Aji (Indonesian Aquaculture Journal, 2011)
Microalgae concentrates (paste) can be used as an alternative feed to replace live microalgae for aquaculture due to its nutritional value and convenience. However, the clumping of cells and negative buoyancy of algae concentrate can affect bivalve culture as bivalves only capture particles suspended in the water and ingest a certain size range of particles. This study investigated the effects of aeration on the distribution of algae particles in a 500 L rearing tank. The results indicated that the number of algae paste particles was higher in the aerated tanks compared to the non-aerated tanks over 24 hours. Time lapsed had a significant effect on the number of particles after the addition of algae concentrate into the tanks. The number of particles in the aerated and non-aerated tank was relatively stable from 1 to 10 hours and then declined after 24 hours. Furthermore, tank depth had no significant effect on the number of particles distributed as the number of particles did not differ significantly at three different depths within the culture tanks.